Behavior of reinforced concrete beams strengthened with anchored FRP sheets under cyclic load reversals - Alshamrani, Salman (Kansas State University, 2024)
The use of carbon fiber reinforced polymer (CFRP) composites is a widely accepted method for externally strengthening reinforced concrete members. However, there is a notable gap in the literature regarding the behavior of CFRP-strengthened beams fiber anchors under reversed cyclic loading. This study addresses this gap by examining the performance of normal and low-strength concrete, with a moderate steel ratio (0.005) and low steel ratio (0.0034), in constructing fourteen identical full-scale rectangular beams. These beams were strengthened with both unanchored and anchored CFRP sheets. Based on the concrete strength, steel ratio, and CFRP scheme, the beams were categorized into three groups. The first group comprised five beams with lightly reinforced steel and low-strength concrete. This group included a control specimen, as well as strengthened specimens with thin sheets with and without fiber anchors and strengthened specimens with thick sheets with and without fiber anchors. The second group replicated the first group in terms of CFRP scheme, but with a moderate steel ratio and higher-strength concrete. The third group consisted of four beams, two with the same lightly reinforced steel and low-strength concrete as those of group 1, and two with the same moderate steel ratio and higher-strength concrete as those of group 2. This third group consisted of two beams strengthened with double thick CFRP sheets top and bottom secured with fiber anchors. The other two were strengthened using a recent patent concept suggesting the use of a small steel plate as a ductility fuse by sandwiching it in between two layers of FRP at the critical plastic hinge region. All specimens underwent cyclic testing under displacement control, following the AC 125 loading protocol (Acceptance Criterion 125, ICC). The failure modes varied among all three groups, including excessive yielding, CFRP sheet debonding, CFRP sheet rupture, shear failure, and cover delamination. The hysteresis response loops of the different specimens were compared, including ultimate capacity, ductility, stiffness degradation, and energy dissipation. Furthermore, this study involved the development of a phenomenological model to predict the response behavior of RC beams subjected to fully reversed loading cycles until failure. The comparative discussion and analysis of the results with the phenomenological model exhibited a promising correspondence. Finally, experimental observations were conducted to investigate the behavior of the structural systems with the indicated innovative materials under reverse cyclic loading, as well as the load-deflection, and the moment-curvature response. These observations aim to establish a basis for future analytical modeling of the hysteresis response of RC beams strengthened with CFRP sheets with and without fiber anchors.
Keywords: Seismic performance; CFRP strengthening; Carbon fiber splay anchors; Flexural members; Hysteresis modeling; Steel fuse